Literature Survey of Privacy Preserving Data Publishing (PPDP) Techniques (International Journal of Engineering and Computer Science, 2017)
​Microdata-Information collected by different organizations is published for analysis to the analyst, decision makers, policy makers and researchers. Original data is not published due to some privacy issues. So, techniques are needed to preserve privacy of data. This paper includes the comparative study of various techniques available to preserve the privacy of published data.